1999
DOI: 10.1111/j.1943-278x.1999.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Postponed Suicide Death? Suicides around Birthdays and Major Public Holidays

Abstract: The relationship between suicide and birthdays, and suicide and public holidays has been studied from data on 32,291 Danish suicides by persons ages 15 years and older in the 25‐year period 1970–1994. Evidence was found to support the theory of the “broken‐promise effect” for major public holidays in that there appears to be a postponement of a significant number of suicides from before a holiday until after. The division of holidays into nonworking and (half‐time) working days showed that a “holiday effect” c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, the results represent a novel minor effect in the seasonality of suicide. This effect is to be located in a category similar to the holidays or birthday effects (28), that is, minor or short-term effects which are lost in the overall seasonal pattern. They are detectable because of large databases and also appropriate statistical modeling.…”
Section: Alternative Interpretationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results represent a novel minor effect in the seasonality of suicide. This effect is to be located in a category similar to the holidays or birthday effects (28), that is, minor or short-term effects which are lost in the overall seasonal pattern. They are detectable because of large databases and also appropriate statistical modeling.…”
Section: Alternative Interpretationsmentioning
confidence: 99%
“…However, recent research suggests that suicide seasonality can be differentiated into distinct seasonalities related to specific suicide methods-drowning, hanging, or jumping from high places-with specific amplitudes and peak-low periods (27). Additional known effects include a holiday/ festive day effect and a birthday effect (28,29), as well as a specific effect for the Advent season (27). Suicide frequencies tend to be particularly low before or on such days.…”
mentioning
confidence: 99%
“…Although weather conditions are not a major cause of suicide, research indicates that suicide rates in both hemispheres reach their maximum in spring and summer and minimum in winter. 42 , 51 - 53 In this study, it is seen that the crude suicide rates are higher in spring and summer months than in other seasons in both genders in suicides of known or unknown cause. Although it is claimed that suicide deaths do not differ according to gender in terms of seasonality in the studies of Oravecz et al 52 and Lee et al, 53 it is observed that the seasonality effect on female suicide is higher in this study, as in the study of Masterton.…”
Section: Discussionmentioning
confidence: 55%
“…Conversely, other studies have reported increased psychological disorders during holidays due to changes in social relationships and interactions [ 20 , 21 ]. Several studies have reported that suicidal behaviors are more common after holidays, following a decrease before and during them, while others have found no temporal patterns at all [ [22] , [23] , [24] , [25] , [26] , [27] ]. In another study, Beauchamp et al found that harmful actions were mainly committed by adults on Sundays and Mondays, whereas individuals younger than 19 tended to prefer Mondays and Tuesdays [ 28 ].…”
Section: Introductionmentioning
confidence: 99%